1984
DOI: 10.1159/000280954
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Some Autonomic Drugs on Spontaneous Contractions of Isolated Dog Ureter

Abstract: Effects of some autonomic drugs on the isolated dog ureteral preparations showing spontaneous contractions were investigated quantitatively. Noradrenaline, adrenaline and phenylephnne produced increases in frequency and tension of the contractions which were reversed to decreases or depressed by phentolamine. Isoproterenol abolished the spontaneous contractions. Acetylcholine did not significantly change frequency and tension of the contractions. The results indicate that ureteral spontaneous contractions may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…These changes were accompanied by an increase in the rate of fluid transport (Kondo et al, 1985;Morita et al, 1987). Furthermore, Yano et al (1984) confirmed this relaxant response of isoprenaline on canine isolated ureteral preparations. These data agree with those found in other structures of urogenital tract such as oviduct, where the stimulation of Padrenoceptors facilitates the transport of the ovum or embryon (Isla et al, 1989).…”
Section: Responses To P-adrenoceptor Agonistssupporting
confidence: 65%
See 2 more Smart Citations
“…These changes were accompanied by an increase in the rate of fluid transport (Kondo et al, 1985;Morita et al, 1987). Furthermore, Yano et al (1984) confirmed this relaxant response of isoprenaline on canine isolated ureteral preparations. These data agree with those found in other structures of urogenital tract such as oviduct, where the stimulation of Padrenoceptors facilitates the transport of the ovum or embryon (Isla et al, 1989).…”
Section: Responses To P-adrenoceptor Agonistssupporting
confidence: 65%
“…Moreover, Yano et al (1984) showed that phentolamine reversed the increased responses induced by noradrenaline to the inhibitory ones in dog isolated middle ureters.…”
Section: Responses To P-adrenoceptor Agonistsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, isolated dog ureters with out spontaneous activity were used as experi mental models, in which rhythmic contrac tions were evoked by an administration of potassium or phenylephrine to confirm parti cipation of calcium influx in the generation of such contractions. The former depolarizes cell membranes [13], and the latter stimu lates adrenergic ct-receptors in smooth mus cle [7,8]. The present observations of evoked ureteral contractions had a rhythm with regu larity and amplitude suggesting that ureteral smooth muscle possesses pace-making prop erties even if short strips of a length of 15 mm are used.…”
Section: Discussionmentioning
confidence: 48%
“…Only some ureteral preparations showed spontaneous contractions [7,8], The present study was carried out on preparations with out spontaneous activity, and the ureteral rhythmic contractions were induced by an addition of potassium (1.5 X 10'2A/) or phenylephrine (3 X 10_5M). Stable rhyth mic contractions continued for 1.5-2.0 h or more.…”
Section: Effects O F D Z On Evoked Ureteral Rhythmic Contractionsmentioning
confidence: 99%